Neo Automatic Code (NAC) To Improve Return Of Spontaneus Circulation (ROSC) In Hospital Cardiac Arrest (IHCA) Patients - Rendi Editya Darmawan; Untung Sujianto; Nana Rochana (JENDELA NURSING JOURNAL, 2021)
Background: a higher rate of recommended chest compression is needed for neo automatic code (NAC)-guided cardiopulmonary resuscitations (CPR) to obtain high-quality chest compressions. High-quality chest compressions could improve ROSC. Purpose: the study aim to analyze the effects of CPR using NAC on the ROSC in-hospital cardiac arrest in Indonesia. Methods: this study used a quantitative, post-test quasi-experimental design with a control group. The samples were 74 cardiac arrest patients in two hospitals in Surakarta and Klaten, Indonesia, who were selected using a purposive sampling technique. The data were analyzed by the Mann-Whitney test. Results: the incidence of ROSC in the control group was 30%, and in the treatment group was 35%. The result of statistical analysis showed that there were differences in the ROSC in the intervention and control group with a p-value of 0.003. Conclusion: NAC assisted cardiopulmonary resuscitations increased ROSC. It is recommended that Code Blue Teams should use NAC to improve the quality of chest compressions for the better result of ROSC.